Quantifying the community capitals framework: Strategic application of the community assets and attributes model. Issue 5 (19th October 2020) - Mueller, Daniel; Hoard, Season; Roemer, Kelli; Sanders, Christina; Rijkhoff, Sanne A. M.
ABSTRACT: The Community Capitals Framework (CCF) has become a significant part of the study of community development, and scholars have used this framework to explore numerous avenues of development. In this paper, we argue that quantification of the CCF's social assets (human, social, cultural, and political capitals) is important for initial assessment of prospective communities for economic development projects and can provide communities and policy makers with the tools to improve on these essential capitals through strategic interventions. We have refined a quantitative model of the four social assets, the Community Assets and Attributes Model (CAAM), that measures human, cultural, social, and political capitals. Through case studies involving the siting of biorefineries and energy plants, we demonstrate the validity and effectiveness of our full model and how we use it to develop strategies to help policy makers and project stakeholders engage with communities and aid in their decision-making process.